ANALISIS KELAYAKAN DAN SWOT OBJEK WISATA PEMANDIAN ALAM TAMAN REKREASI GOTONG ROYONG INDAH DI DESA HULU, KECAMATAN PANCURBATU, KABUPATEN DELI SERDANG, PROVINSI SUMATERA UTARA - Chandra Rikardo Simanjuntak; Pindi Patana; Kansih Sri Hartini (Program studi Kehutanan USU, 2016)
Taman Rekreasi Gotong Royong Indah is a destination located in Pancurbatu. One of the benefits that can be gained is the development of natural areas for ecotourism. This study aimed to (1) analyze the potential attraction of Taman Rekreasi Gotong Royong Indah (2) to analyze the problems of nature tourism development strategy in the region. This research used Analysis SWOT. The result showed that the attraction of Taman Rekreasi Gotong Royong Indah has potential to be developed on the level of 76,04% and the feasibility of the SWOT analysis in quadran I, that means it has strength and opportunities that can be developed as tourist attraction. Keyword : development,Deli Serdang District